EFFICIENCY OF ORTHOPEDIC CLEANING OF HORSES’ HOOVES - Kulynych, S.; Kramarenko, V.; Zezekalo, M.; Omelchenko, A.; Аvramenko, N. (Scientific Progress & Innovations, 2022)
The health of horses is largely determined by the condition of the hooves, so the limbs of these noble animals require special attention. Regular care is required to prevent hoof diseases, including: daily inspection and cleaning under running water; untwisting; treatment with special ointments (if necessary). Regular care not only prevents the development of many pathologies, but also allows you to notice dangerous signs – cracks, bruises, punctures, purulent formations. Hoof trimming is carried out in order to prevent hoof disease, create normal conditions for the growth of hoof horns and prevent various mechanical damage. Running hoof disease can cost a horse his life, and accurate diagnosis and treatment require special skills. The aim of the work was to identify existing deformities of horses’ hooves, to develop orthopedic cleaning techniques depending on the type of deformation. The research was conducted on the basis of horse farms of Kyiv region "KK ‒ delight", "Golden Horseshoe" and PE "Metal Horse". Hoof deformation was determined on the basis of clinical examination and hoof measurements using special equipment. The obtained data were included in the protocol of the clinical study of the animal. After determining the type of deformation, orthopedic hoof cleaning was performed in 7 stages. During cleaning, the deformed hoof was inspected and heated with a gas heater to soften its shell. Subsequently, mechanical cleaning of the sole surface was performed and areas of exfoliated horn were removed. At the next stage, the sole was trimmed, followed by removal of the posterior walls and the formation of an arrow by peeling off the excess of the hoof wall. This procedure allowed creating an even distribution of the load on the sole by balancing it. The manipulation was repeated after 35‒55 days. If necessary, the latero-medial imbalance of the hooves after assessment of their condition was corrected. These manipulations in the proposed sequence are logical, extremely simple to perform and allow you to prevent the occurrence of pathologies of the distal extremities of horses.